Rivalitas Negara Adidaya di Ruang Angkasa - Situmorang, Veronica Marsaulina (Department of International Relations, Brawijaya University, 2020)
International relations not only focused on cooperative relations but also rivalry relationships that characterize the existence of competition to create progress in the global system, whose primary goal is to prioritize the domestic interests of each competing state actor. With all the demands for existing renewal, the modern world makes every country compete fiercely to show self-esteem as a great country. After the cold war, the source of world power has grown from being bipolar, namely the United States and the Soviet Union, to becoming multipolar. This paper will focus on the competition between the United States, and one of the countries predicted to become a new center of power in the international world, namely China. China's rapid progress in various fields has made it even more calculated and has become a new threat to the US as a superpower. Not only the economy and defense, now China's progress is starting to develop in the field of space control, and this is increasingly making the US-China rivalry relationship even more complex. This paper will be explained with a descriptive-qualitative research method that tries to describe in-depth and narrate the form of competition between the United States and China in the control of space and its astropolitics strategy